Haemorrhage at caesarean section: a framework for prevention and research. Issue 6 (December 2016) - Jardine, Jennifer E.; Law, Penny; Hogg, Matthew; Murphy, Deirdre; Khan, Khalid S.; ,
Abstract : Purpose of review: Caesarean section rates are increasing across the world. Postpartum haemorrhage is a major cause of morbidity and mortality; major haemorrhage is more common after caesarean delivery. There is a wide range of practice in the prevention and treatment of postpartum haemorrhage at caesarean section. The aim of this review is to summarize current opinion in the management of postpartum haemorrhage at caesarean section. Recent findings: Recent large randomized controlled trials have shown a possible effect from the routine use of tranexamic acid and ergometrine. Small randomized controlled trials have shown a possible benefit from using carbetocin. Summary: The impact of postpartum haemorrhage can be reduced by antenatal correction of anaemia. Intraoperative medical management consists of oxytocinon, additional oxytocics +/− tranexamic acid, with at present limited evidence as to the order in which these should be considered. Trials of routine use of cell salvage and tranexamic acid are currently underway.